BIOLOGICAL ACTIVITY AND THERAPEUTIC PROPERTIES OF MATRICARIA CHAMOMILLA L - Bilovol, O.M.; Knyazkova, I.I.; Bilovol, A.M.; Kondrusyk, N.Y.; Kuzminova, N.V.; Molodan, D.V.; Abramova, L.P. (World of Medicine and Biology, 2025)
Matricaria chamomilla L. is one of the most widely used medicinal plants. The main components of the flowers include phenolic compounds, mainly the flavonoids apigenin, quercetin, patuletin, luteolin and their glucosides; the main components of the essential oil extracted from the flowers are the terpenoids α-bisabolol and its oxides and azulenes, including chamazulene. Components of Matricaria chamomilla L., such as α-bisabolol, β-farnesene, chamazulene, apigenin, geraniol, gerniarin, umbelliferone, luteolin, quercetin, and rutin, are believed to have anti-inflammatory effects. It has been established that α-bisabolol of Matricaria chamomilla gives it antimicrobial properties against both Gram-positive and Gram-negative bacteria. Chamomile (Matricaria chamomilla) has been used since ancient times to treat various skin lesions such as burns and wounds. To date, it has been established that the biologically active substances of Matricaria chamomilla L. have antioxidant, antispasmodic, analgesic, anti-inflammatory, antiseptic, diaphoretic, choleretic effects; reduce allergic reactions, enhance regeneration processes, increase the secretory activity of the digestive glands, stimulate appetite, eliminate intestinal spasms, and reduce fermentation processes. The chemically active components of essential oils, or volatile oils, have been shown to have neuroprotective effects, which may help alleviate symptoms of depression and anxiety. The long-term use of chamomile in clinical medicine has shown the numerous effects of this medicinal plant, which are due to the powerful potential of biologically active substances, a wide spectrum of biological and pharmacological activity and proven efficacy, along with good tolerability.